2021
DOI: 10.21203/rs.3.rs-404809/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nodal superconductivity and superconducting domes in the topological Kagome metal CsV3Sb5

Abstract: Recently superconductivity was discovered in the Kagome metal AV3Sb5 (A = K, Rb, and Cs), which has an ideal Kagome lattice of vanadium1-4. These V-based superconductors also host charge density wave (CDW)5 and topological nontrivial band structure2,6, thus provide a great platform to study the interplay of superconductivity, CDW, frustration, and topology. Here we report the ultralow-temperature thermal conductivity and high pressure resistance measurements on CsV3Sb5 with Tc ≈ 2.5 K, the highest among AV3Sb5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Shapley value method is a method of interest distribution in cooperative Game theory, which can scientifically and fairly distribute the interests of each unit according to the degree of contribution, and obtain the weight value of each unit (Li et al, 2021). This allocation approach can be well reflected in combination prediction.…”
Section: Shapley Value Methods Combined Prediction Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Shapley value method is a method of interest distribution in cooperative Game theory, which can scientifically and fairly distribute the interests of each unit according to the degree of contribution, and obtain the weight value of each unit (Li et al, 2021). This allocation approach can be well reflected in combination prediction.…”
Section: Shapley Value Methods Combined Prediction Theorymentioning
confidence: 99%
“…et al, 2023). Li et al (2021) combined the individual characteristic weight coefficient with the Shapley value of each hydropower station, and proposed a variable coefficient Shapley value method for compensation benefit distribution of multi owner cascade hydropower stations. Taking China's Nanhe Hydropower Station as an example, this method was compared with other typical distribution methods.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, fruitful experiments have been actualized to understand the superconducting gap symmetry of CsV 3 Sb 5 , including thermal conductivity 18 , scanning tunneling spectroscopy measurements 19 , and penetration length measurements 20 . However, these results provided contradictory conclusions on the gap symmetry [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . On the other hand, since the superconductivity coexists with CDW, their interplay should be also taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, however, the superconducting gap symmetry of AV 3 Sb 5 is highly controversial, and whether TRS is broken or not is still elusive. Thermal conductivity measurements in CsV 3 Sb 5 [29] and µSR measurements in Rb/KV 3 Sb 5 [30] have suggested a nodal gap structure. In contrast, magnetic penetration depth [31] and scanning tunneling spectroscopy (STS) [32] studies in CsV 3 Sb 5 have suggested a nodeless gap structure.…”
mentioning
confidence: 99%